Some Fixed-Point Results via Mix-Type Contractive Condition - Özlem Acar (Journal of Function Spaces)
We consider a fixed-point problem for mappings involving a rational type and almost type contraction on complete metric spaces. To do this, we are using F-contraction and H,φ-contraction. We also present an example to illustrate our result.